Advanced mare age impairs the ability of in vitro‐matured oocytes to correctly align chromosomes on the metaphase plate. (9th August 2018) - Rizzo, M.; Ducheyne, K. D.; Deelen, C.; Beitsma, M.; Cristarella, S.; Quartuccio, M.; Stout, T. A. E.; de Ruijter‐Villani, M.
Summary: Background: Advanced mare age is associated with declining fertility and an increased risk of early pregnancy loss. Compromised oocyte quality is probably the primary reason for reduced fertility, but the defects predisposing to embryonic death are unknown. In women, advanced age predisposes to chromosome segregation errors during meiosis, which lead to embryonic aneuploidy and a heightened risk of miscarriage. Objectives: To evaluate the effect of advanced mare age on chromosome alignment and meiotic spindle morphology in in vitro‐matured (IVM) oocytes. Study design: Morphometric and morphological analysis. Methods: To investigate differences in spindle organisation and chromosome alignment between young and old mares, oocytes collected from slaughtered mares were divided into two groups depending on mare age (young, ≤14 years and old, ≥16 years), IVM and stained to visualise chromatin and alpha‐tubulin. Spindle morphology, morphometry and chromosome (mis)alignment were evaluated by confocal microscopy and 3D image analysis. Results: Oocytes from old mares showed a higher incidence of chromosome misalignment (47.4% vs. 4.5%; P<0.001) and a thicker metaphase plate (mean ± s.d.: 5.8 ± 1.0 μm vs. 4.9 ± 0.9 μm; P = 0.04) than oocytes from young mares. Although no differences in spindle morphometry were detected between old and young mares, an increased major spindle axis length was associated with chromosome misalignment (mean ± s.d.: 25.3 ± 6.1 μm vs. 20.8 ± 3.3 μm; P = 0.01) irrespective of age. Main limitations: The oocytes were IVM and may not exactly reflect chromosome misalignment in vivo. Conclusions: Advanced mare age predisposes to chromosome misalignment on the metaphase II spindle of IVM oocytes. The compromised ability to correctly align chromosomes presumably predisposes to aneuploidy in resulting embryos and thereby contributes to the age‐related decline in fertility and increased incidence of early pregnancy loss. The Summary is available in Portuguese – see Supporting Information